Unveiling the energy consumption-food waste nexus in households: A focus on key predictors of food waste generation - (:unkn) unknown (Springer Nature Japan, 2024)
In most cities worldwide, household food waste constitutes a significant portion of municipal solid waste (MSW). However, its management often proves inadequate due to the insufficient resources allocated to waste management systems, the omission of the ...
Keywords: Desperdicio de alimentos; Consumo energético